Analysis of THz generation through the asymmetry of photoelectron angular distributions - Zhou, Zhaoyan; Wang, Xu; Lin, C. D. (My University, 2017)
We analyze the mechanism of THz generation in a gas medium with intense two-color infrared lasers pulses. The dependence of the amplitude of THz emission on the relative phase between the fundamental color (800 nm) and its second harmonic (400 nm) is shown to be identical to the residual current as well as to the asymmetry of the above-threshold-ionization (ATI) photoelectrons along the left versus the right side of the linear polarization axis of the laser, thus confirming the validity of the semiclassical photocurrent model for the THz emission. We further analyze the even vs odd angular momentum distributions of the ATI electrons. The degree of overlap between the even-parity dominant electrons and the odd-parity dominant electrons within each ATI peak determines the strength of the THz emission, thus favoring the model that THz is generated through free-free transitions in the laser field. A model is also provided to obtain the same phase dependence as the four-wave mixing model.